Smoking and Lung Cancer: A Geo-Regional Perspective - Rahal, Zahraa; El Nemr, Shaza; Sinjab, Ansam; Chami, Hassan; Tfayli, Arafat; Kadara, Humam (Frontiers in Oncology, 2017)
Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) represents the most frequently diagnosed subtype of this morbid malignancy. NSCLC is causally linked to tobacco consumption with more than 500 million smokers worldwide at high risk for this fatal malignancy. We are currently lagging in our knowledge of the early molecular (e.g., genomic) effects of smoking in NSCLC pathogenesis that would constitute ideal markers for early detection. This limitation is further amplified when considering the variable etiologic factors in NSCLC pathogenesis among different regions around the globe. In this review, we present our current knowledge of genomic alterations arising during early stages of smoking-induced lung cancer initiation and progression, including discussing the premalignant airway field of injury induced by smoking. The review also underscores the wider spectra and higher age-adjusted rates of tobacco (e.g., water-pipe smoke) consumption, along with elevated environmental carcinogenic exposures and relatively poorer socioeconomic status, in low-middle-income countries (LMICs), with Lebanon as an exemplar. This “cocktail” of carcinogenic exposures warrants the pressing need to understand the complex etiology of lung malignancies developing in LMICs such as Lebanon.